A Comparative Study of Social Skills between Students with Hearing Aid Users and Cochlear Implants - Ashish Kumar Singh; Dr. Deepak Pancholi (International Journal of Scientific Research in Science, Engineering and Technology, 2025)
The purpose of this study was to compare the social skills of students with hearing aid users and cochlear implants to understand how these assistive devices/technologies influence social development and interactions. The Social skills play a crucial role for academic success, peer relationships, and overall well-being, particularly for students with hearing impairments. The research involves combining quantitative assessments with qualitative insights. This study involved 60 bilateral sensorineural hearing impaired students whose age range between 6-15 years. Thirty hearing impaired students had moderately severe/severe hearing loss with hearing aid users and 30 hearing impaired students severe to profound hearing loss with cochlear implants, drawn from special schools, inclusive schools and specialized clinics. Social skills and interactions were assessed using standardized test i.e. Vineland Social Maturity Scale (VSMS), focusing on communication abilities, peer interactions, and adaptive behaviours in various social settings. The findings suggest that students with cochlear implants demonstrate higher proficiency in verbal communication and peer engagement compared to their hearing aid-using counterparts, potentially due to enhanced auditory input and speech perception. However, students using hearing aids showed comparable performance in non-verbal communication and social adaptation. The study highlights the importance of tailored social skills training and support services to meet the unique needs of both groups. These insights can guide educators, therapists, and policymakers in developing inclusive educational strategies and interventions to enhance the social development of students with hearing impairments.
Keywords: Hearing aids; cochlear implants; hearing impairment; communication; social skills